TEACHER’S DIFFICULTIES IN TEACHING JAPANESE WRITING SYSTEM (SAKUBUN) - Handini, Baiq Suprapti (LPPM Universitas Bumigora Mataram, 2018)
This paper aims to describe the problem of teacher in teaching japanese writing sytem (sakubun). Write the letter of japanese, Hiragana, katakana, and kanji will be the most difficult thing. Writing skills are necessary to develop students’ practical communication abilities. Teacher is an important person in learning process. The role of the teacher is diverse and has several orientations. One important aspect is that of facilitator of student learning. The facilitator attempts to provide circumstances that will enable students to engage with the learning opportunities and construct for themselves their understandings and skills. That’s why teacher should offered how to solve a japanese students problem in writing.